Asymptomatic Neuropathy in Recently Diagnosed Diabetic Patients: Electrophysiological Evaluation (Bangladesh Journal of Neuroscience, 2014)
Aim & background: As significant electrophysiological changes are found in asymptomatic neuropathy in diabetes mellitus and electrophysiological studies of nerve conduction velocity are our most sensitive tools to quantify early abnormalities, therefore, we tried to find out status of asymptomatic peripheral nerve dysfunction in recently diagnosed diabetic patients in Bangladesh perspective. Method :This study was carried out at BSMMU and BIRDEM during November 2005 and April 2006. The study included 60 subjects, 30 recently diagnosed diabetic subjects (14 male, 16 female). None had neuropathic symptoms or signs. All cases were selected randomly diagnosed by ADA criteria accepted by WHO. Thirty healthy controls with mean age comparable to that of diabetic subject were selected from the friends of the subjects and patients attending neurology outdoor of BSMMU. Result:Findings (mean±SD) were (case and control, respectively): Tibial nerve, DML 4.05±0.81 and 3.84±0.70 msec (P>0.10), CMAP 16.90±5.14 and 19.49±4.73 mV (P0.50), CMAP 5.80±2.89 and 6.97±1.79 mV (P>0.05), MCV 43.10±8.89 and 48.27±3.56 m/s (P0.10) and MCV 55.16±5.33 and 57.70±4.33 m/s (P0.50); and ulnar nerve DML 2.57±0.33 an 3.17±0.61 msec (P0.05), MCV 55.74±5.00 and 58.50±5.13 m/s (P0.50); sural nerve, DSL 2.46±0.68 and 3.12±0.45 msec (P0.50); and ulnar nerve, DSL 2.03±0.39 and 2.48±0.49 msec (P0.50), and SCV 60.96±8.38 and 57.93±7.15 m/s (P>0.10). Mean (±SD) HbA1c was significantly high (P